SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ASURANSI JIWA MENGGUNAKAN PENDEKATAN METODE ANALYTIC HIERARCHY PROCESS - Arif Susanto; puput irfansyah (LPPM, 2016)
Abstract. Development of insurance business in the current rapidly evolving, where this can create confusion in determining the prospective customer to choose an insurance option that suits their wants and needs. Life insurance is a business in the services it provides assurance to its customers when they experience the events that are at risk of missing its productivity be financial. However, most customers are actually regret having become insurance customers due to their lack of understanding for insurance itself. Computer-based information systems can be used in solving the problem of decision-making is often called a decision support system that can help everyone in the choice of a problem that will be faced. The method can be used in the selection of life insurance is graded analysis process method wherein each alternative will be made perengkingan to obtain the best results. With the help of software end result sorting system in the form of a life insurance company that is used as a tool in decision making for potential customers. Decision support system is expected to help prospective customers to choose the right life insurance and in accordance with needs.Keywords: Decision Support System, Life Insurance, Analytic Hierarchy Process